Latin American Spanish phrase book & dictionary - Sekhavati, Zara (Berlitz Publishing, 2019)
This clear, compact phrase book for travellers is packed with key words and phrases to help conversation. The pocket-sized Latin American Spanish phrasebook and dictionary from Berlitz's language experts (with free app) is a trusty travel companion. It's all you need to make yourself understood - and to understand others - when you're out and about.